Routinely Performed Serial Follow-Up Imaging in Asymptomatic Patients With Multiple Cerebral Cavernous Malformations Has No Influence on Surgical Decision Making - Velz, Julia; Stienen, Martin Nikolaus; Neidert, Marian Christoph; Yang, Yang; Regli, Luca; Bozinov, Oliver (Frontiers in Neurology, 2018)
Background: The best strategy to perform follow-up of patients with multiple cerebral cavernous malformations (mCCM) is unclear due to the unpredictable clinical course. Still, serial radiological follow-up is often performed. The objective of this work was to critically question whether active follow-up by serial imaging is justified and has an impact on clinical decision making. Methods: We included all consecutive patients with mCCM treated and followed at our Department between 2006-2016. Patient data were collected and analyzed retrospectively. Results: From a total number of 406 patients with CCM, n = 73 (18.0 %; mean age at first diagnosis 45.2 years (± 2.4 SE); n = 42 male (57.5 %)) were found to harbor multiple lesions (≤5 CCM in 58.9 %; 6-25 in 21.9 %; ≥ 25 in 19.2 %). All of them were followed for a mean of 6.8 years (± 0.85 SE). Conservative treatment was suggested in 43 patients over the complete follow-up period. 30 patients underwent surgical extirpation of at least one CCM lesion. 43 surgical procedures were performed in total. During 500.5 follow-up years in total, routinely performed follow-up MRI in asymptomatic patients lead to an indication for surgery in only 2 occasions and even those 2 were questionable surgical indications. Conclusion: Routinely performed follow-up MRI in asymptomatic patients with mCCM is highly questionable as there is no evidence for therapeutic relevance.